Faith and Revolution: The Case of Islamic Resurgence by Said Nursi in Turkey - Qaisar Mohammad (Analisa: Journal of Social Science and Religion, 2020)
Bediuzzaman Said Nursi dedicated his life to the safeguarding and strengthening of faith in God, which for him was the most important issue of the time and was at the heart of religion and the societal system. He believed religious conviction faced severe and combined attacks and was being weakened by unreligious ideologies. Nursi sought to strengthen belief by transforming it from imitation to certainty. He maintained that to be occupied with the fundamentals of belief over and above everything was an absolute necessity and compelling need. This deﬁnition of the problem gave direction to his discourse, and in all his writings Nursi pursued the renewal, revival, and strengthening of the truths of creed, rather than trying to rebuild Islamic political authority and Islamic institutions or expounding Islamic Shariah rules. This is the most important single issue that distinguishes Nursi from his contemporaries. This paper, in this backdrop, anticipates to discuss the signiﬁcance of Nursi’s thoughts, teachings and also explains the importance of Nursi in the formation of ideology that helped the society of Turkey to neutralize anti-religious systems. The aim of this research paper is to explain Nursi’s contributions that proved him to be a faith revivalist and whose works are one of the most ubiquitous read materials in Turkey. This essay is primarily a theoretical one and the methodology adopted for this paper is analytical-historical and descriptive.